Managing Fragile Regions Method and Application - Guo, Rongxing; Freeman, Carla (Springer New York Imprint: Springer, 2011)
This book gathers the work of leading scholars from several disciplines on fragile regions, especially those regions seeking to preserve, strengthen or create processes to restore or reestablish security and effective social and economic management. It tackles the multifarious issues that shape and affect fragile regions, drawing upon a wide range of intellectual and methodological approaches, including such fields as area studies, natural resource science, biology, environmental and resource economics and management, and political economy. The volume brings together the perspectives of a diverse group of contributors from Australia, China, Hong Kong, Indonesia, Japan, South Korea, and the United States. Managing Fragile Regions: Method and Application addresses a variety of factors ? natural, political, administrative, legislative, economic, social, and cultural ? and examines how they exert influences on the operational mechanisms of fragile regions, especially in the contexts of peace and security, economic development, and environmental management. The volume?s nine chapters cover a wide range of examples of fragile regions and their challenges. It will be of interest and utility to practitioners and policy-makers engaged in disaster management and post-disaster reconstruction. Students, researchers, and other professionals involved in resource management, regional science, and environmental science will also find it valuable reading.